Oryza sativa mediator subunit OsMED25 interacts with OsBZR1 to regulate brassinosteroid signaling and plant architecture in rice. Issue 6 (25th February 2020) - Ren, Yuekun; Tian, Xiaojie; Li, Shuyu; Mei, Enyang; He, Mingliang; Tang, Jiaqi; Xu, Min; Li, Xiufeng; Wang, Zhenyu; Li, Chuanyou; Bu, Qingyun
Abstract: Brassinosteroids (BRs) are plant‐specific steroid hormones which regulate plant growth, development, and adaptation. Transcriptional regulation plays key roles in plant hormone signaling. A mediator can serve as a bridge between gene‐specific transcription factors and the RNA polymerase machinery, functioning as an essential component in regulating the transcriptional process. However, whether a mediator is involved in BR signaling is unknown. Here, we discovered that Oryza sativa mediator subunit 25 (OsMED25) is an important regulator of rice BR signaling. Phenotypic analyses showed that the OsMED25‐RNAi and osmed25 mutant presented erect leaves, as observed in BR‐deficient mutants. In addition, the OsMED25‐RNAi and osmed25 mutant exhibited decreased BR sensitivity. Genetic analysis indicated that OsMED25‐RNAi could suppress the enhanced BR signaling phenotype of Osbzr1‐D . Further biochemical analysis showed that OsMED25 interacts with OsBZR1 in vivo, and OsMED25 is enriched on the promoter of OsBZR1 target genes. RNA sequencing analysis indicated that OsMED25 affects the expression of approximately 45% of OsBZR1‐regulated genes and mainly functions as a corepressor of OsBZR1. Together, these findings revealed that OsMED25 regulates rice BR signaling by interacting with OsBZR1 and modulating the expression of OsBZR1 target genes, thus expanding our understanding of the roles of mediators in plant hormone signaling. Abstract : Plant hormone BR controls the rice architecture and final yield. Ideal plant architecture of rice can be bred via manipulating BR signaling. We show that OsMED25 regulates rice BR signaling by interacting with OsBZR1 and modulating the expression of OsBZR1 target genes, which provide a putative target for engineering breeding.